The Exemplary Implementation of Islamic Religious Education Teachers in Optimizing Student Moral Development - Rosyid, Ahmad Sihabudin; Irhamuddin, Irhamuddin; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The aim of this research is to examine how the moral growth of class XI students at Tri Bhakti Attaqwa Vocational School is maximized through the use of extraordinary Islamic Religious Education (PAI) teachers. This research uses qualitative methodology, collecting data through documentation, interviews and observation. The research results show that the example of PAI teachers plays an important role in shaping students' morals through attitudes, behavior and teaching methods. Key supporting factors include teachers' commitment to integrating moral values into teaching and school activities and a supportive school environment. However, barriers such as limited parental involvement and inadequate facilities for moral education were also identified. This study recommends increasing collaboration between schools and parents and developing value-based programs to support optimal student character development.